Smart Production Workers in Terms of Creativity and Innovation: The Implication for Open Innovation - Bożena Gajdzik; Radosław Wolniak (Journal of Open Innovation: Technology, Market and Complexity, 2022)
This paper presents a framework of employee skills and competencies useful for developing occupational profiles for employees of companies transitioning towards Industry 4.0. The paper consists of a discussion of the theoretical and practical parts of case studies. The theoretical portion was created on the basis of a review of scientific literature and research studies regarding the competencies and skills of employees in the ongoing fourth industrial revolution. This part focuses on the skills profile of an Industry 4.0 employee and an Operator 4.0 (O4.0) from a creativity and innovativeness point of view. The link between the theoretical part and the case study analysis was a general framework for building the competencies and skills of the steelworker in the emerging fourth industrial revolution. The case study analysis covered the framework of competencies and skills of a metallurgist in smart manufacturing built into the organization of steel mills. Recruitment offers of a steel company implementing smart manufacturing (SM) projects and educational programmes of technical universities in the field of metallurgy were analysed. The aim of the study was to develop a framework for the profile of an employee working in an innovative company transforming to I4.0. The publication posed the following research questions (purposes/hypotheses): P1. To what extent do Polish companies in the metallurgical sector pay attention to creativity and innovation issues when looking for employees? P2. To what extent do the profile (portfolio) of metallurgy graduates of Polish technical universities turn their attention to the issues related to creativity and innovation?